Evaluation of Alternative High-Throughput Sequencing Methodologies for the Monitoring of Marine Picoplanktonic Biodiversity Based on rRNA Gene Amplicons - Ferrera, Isabel; Giner, Caterina R.; Reñé, Albert; Camp, Jordi; Massana, Ramon; Gasol, Josep M.; Garcés, Esther (Frontiers in Marine Science, 2016)
Sequencing of rRNA gene polymerase chain reaction amplicons (rRNA tags) is the most common approach for investigating microbial diversity. The recent development of high-throughput sequencing (HTS) technologies has enabled the exploration of microbial biodiversity at an unprecedented scale, greatly expanding our knowledge on the microbiomes of marine ecosystems. These approaches provide accurate, fast and cost efficient observations of the marine communities, and thus, may be suitable tools in biodiversity monitoring programs. To reach this goal, consistent and comparable methodologies must be used over time and within sites. Here, we have performed a cross-platform study of the two most common HTS methodologies, i.e. 454-pyrosequencing and Illumina tags to evaluate their usefulness in biodiversity monitoring and assessment of environmental status. Plankton biodiversity has been compared through both methodologies by sequencing the 16S and 18S rRNA genes of a set of samples collected in the coast of Barcelona (NW Mediterranean). The results show that, despite differences observed in the rare OTUs retrieved, both platforms provide a comparable view of the marine picoplankton communities. On a taxonomic level, there was an accurate overlap in the detected phyla between the two methods and the overall estimates of alpha- and betadiversity were comparable. In addition, we explored the concept of ‘indicator species’ and found that certain taxa (i.e. members of the Gammaproteobacteria among others) as well as the ratio between some phylogenetic groups (i.e. the ratio of Alphaproteobacteria / Gammaproteobacteria, Alteromonas / SAR11 and Alteromonas + Oceanospirillales / SAR11) have potential for being useful indicators of environmental status. The data show that implementing new protocols and identifying indicators of environmental status based on rRNA amplicon sequencing is feasible, and that is worth exploring whether the identified indices are universally applicable.